Daily field checking list by Walter Rosene, April 26, 1931 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated April 26, 1931. This checklist was used by Walter Rosene to record birds sighted around Boone County with Bob Walker between 6:00 and 9:00. Plustek--flatbed